The role of the nurse in the care and management of patients with atopic dermatitis - Harmieke van Os-Medendorp; Elfie Deprez; Nele Maes; Sheila Ryan; Karina Jackson; Tonya Winders; Linda De Raeve; Christa De Cuyper; Steven Ersser (BMC, 2020)
Abstract Background The purpose of this paper is to provide an overview of key aspects of specialised dermatology nursing practice in the management of patients with moderate to severe atopic dermatitis. The role of dermatology nurse specialists in supporting patients and promoting disease understanding, education and treatment adherence continues to evolve. As features of specialised nursing care can also inform other nursing staff in a wide range of care settings, an overview of key components is examined. Observations presented are from a pan-European perspective and represent the collected view of a group of dermatology nurse specialists, dermatologists and patient advocates following two round-table discussions. Main body Atopic dermatitis is a common, chronic, inflammatory disease characterised by erythematous/scaling skin lesions, with often intense pruritus. Disease course is cyclic with periodic disease flares of varying intensity, presenting management challenges to patients and families. Dermatology nurse specialists play a key role in providing education and substantial patient support to improve treatment outcomes and quality of life to patients and their family, delivered within a multidisciplinary team framework. Nurse-led education and 'eczema schools' are of benefit in reducing disease severity and improving quality of life by enhancing self-management, adherence and patient engagement. eHealth tools, such as patient portals or online training platforms, can provide online learning, individualised education, and help to improve engagement. These and other initiatives, such as written action plans, are all essential to improve or maintain treatment adherence, self-management and quality of life. Conclusions Dermatology nurse specialists play a central role in the assessment and management of moderate to severe atopic dermatitis patients and families. This places them in an ideal position to build strong and often long-term relationships with patients and parents. Such engagement promotes trust, assists in setting realistic expectations of treatment and outcomes, and enhances self-management and engagement in their own care. Providing emotional support, as well as formal and systematic education (including individualised practical advice) all contribute to improved treatment adherence and can enhance the quality of life of patients and their families throughout the course of this long-term condition.